Halal poultry slaughter technology: A critical review of control points - R. Mylostyvyi; V. Lykhach; B. Gutyj; O. Marenkov; D. Mylostyva (Тваринництво та технології харчових продуктів, 2025)
Halal production holds substantial potential for further development, driven by the growing global demand for high-quality, safe, and ethically produced food products. In addition to meeting the needs of Muslim consumers, certified halal products are increasingly appealing to a broader audience that values compliance with high standards of hygiene, traceability, and quality. Modern trends highlight the importance of adhering to stringent requirements, enhancing the competitiveness of halal production in international markets. This literature review examined the technological process of poultry slaughter with a focus on compliance with halal standards and requirements. The study aimed to identify risks at each stage of production, assess their impact on product quality, and propose strategies to optimise production processes in accordance with Islamic standards. The analysis was based on a review of contemporary scientific literature, certification standards, and risk management practices in food production. Key risks are associated with pre-slaughter inspection, stunning, slaughter, bleeding, evisceration, chilling, and post-mortem inspection. It was found that violations at these stages may lead to mechanical damage to carcasses, insufficient bleeding, microbial contamination, or non-compliance with religious standards. Implementing risk management systems, such as HACCP, and adopting modern traceability technologies, including RFID tags and blockchain, can improve transparency, production efficiency, and compliance with international standards. The value of this study lies in identifying directions for improving process control systems, particularly through the integration of automated solutions for monitoring critical points and analysing product quality. The findings may prove useful for raising awareness about poultry slaughter quality requirements in halal-certified production. Future research prospects include the enhancement of slaughter technologies, the development of automated control systems, and the optimisation of quality assessment methods to improve production efficiency and ensure compliance with high hygienic and religious standards